Electroacupuncture Pretreatment Alleviates Cerebral Ischemic Injury Through α7 Nicotinic Acetylcholine Receptor-Mediated Phenotypic Conversion of Microglia - Ma, Zhi; Zhang, Zengli; Bai, Fuhai; Jiang, Tao; Yan, Chaoying; Wang, Qiang (Frontiers in Cellular Neuroscience, 2019)
Electroacupuncture (EA) pretreatment alleviates cerebral ischemic injury through α7 nicotinic acetylcholine receptor (α7nAChR). We attempted to investigate whether the phenotypic conversion of microglia was involved in the therapeutic effect of EA pretreatment in cerebral ischemia through α7nAChR. Adult male Sprague Dawley (SD) rats were subjected to middle cerebral artery occlusion (MCAO) after EA or α7nAChR agonist N-(3R)-1-Azabicyclo[2.2.2]oct-3-yl-furo[2,3-c]pyridine-5-carboxamide hydrochloride (PHA-543,613 hydrochloride) and antagonist α-bungarotoxin (α-BGT) pretreatment. Primary microglia were subjected to drugs pretreatment and oxygen-glucose deprivation (OGD). The expression of the classical activated phenotype (M1) microglia markers induced nitric-oxide synthase (iNOS), interleukin-1β (IL-1β), and cluster of differentiation 86 (CD86), the alternative activated phenotype (M2) microglia markers arginase-1 (Arg-1), transforming growth factor-β1 (TGF-β1), and cluster of differentiation 206 (CD206), and the pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and anti-inflammatory cytokines interleukin-4 (IL-4), interleukin-10 (IL-10) in the ischemic penumbra or in the supernatant of primary microglia were analyzed. The infarction volume and neurological scores were assessed 72 h after reperfusion. The cell viability and lactose dehydrogenase (LDH) release of neurons co-cultured with microglia were analyzed using cell counting kit-8 (CCK8) and LDH release assays. EA pretreatment decreased the expression of M1 markers (iNOS, IL-1β and CD86) and pro-inflammatory cytokines (TNF-α and IL-6), while increased the expression of M2 markers (Arg-1, TGF-β1 and CD206) and anti-inflammatory cytokines (IL-4 and IL-10) by activating α7nAChR. EA pretreatment also significantly reduced the infarction volume and improved the neurological deficit. The activation of α7nAChR in microglia relieved the inflammatory response of primary microglia subjected to OGD, and attenuated the injury of neurons co-cultured with microglia. In conclusion, EA pretreatment alleviates cerebral ischemic injury through α7nAChR-mediated phenotypic conversion of microglia, which may be a new mechanism for the EA pretreatment-induced neuroprotection against cerebral ischemia.